2009
DOI: 10.1038/emboj.2009.127
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor C/EBPβ isoform ratio regulates osteoclastogenesis through MafB

Abstract: Disequilibrium between bone-forming osteoblasts and bone-resorbing osteoclasts is central to many bone diseases. Here, we show that dysregulated expression of translationally controlled isoforms of CCAAT/enhancerbinding protein b (C/EBPb) differentially affect bone mass. Alternative translation initiation that is controlled by the mammalian target of rapamycin (mTOR) pathway generates long transactivating (LAP*, LAP) and a short repressive (LIP) isoforms from a single C/EBPb transcript. Rapamycin, an inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
141
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(146 citation statements)
references
References 75 publications
3
141
0
Order By: Relevance
“…Smink et al showed earlier how C/EBPβ differentially affects bone mass [11]. The group found that rapamycin inhibited osteoclast generation from monocyte precursors in wild-type mice.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Smink et al showed earlier how C/EBPβ differentially affects bone mass [11]. The group found that rapamycin inhibited osteoclast generation from monocyte precursors in wild-type mice.…”
mentioning
confidence: 99%
“…How can we tie these components together? The answers follow years of effort from the Leutz laboratory [9][10][11][12][13]. The story begins with their elucidation of how translational control of C/EBPβ isoforms is regulated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, IL)17A promotes the fusion of DCs, resulting in the multinucleated bone resorbing giant cells in Langherans histiocytosis while enhances the sensitivity of OC precursors to RANK)L (11,12) IL)17A stimulates with high affinity the IL)17RA that drives the OC)like transdifferentiation of iDCs through the CEBPB (CCAAT/enhancer)binding protein beta) factor, thus leading the transcription of NFATc1 (nuclear factor of activated T)cells, cytoplasmic))1, MITF (microphthalmia) associated transcription factor) and cFos while modulates MAFB (musculoaponeurotic fibrosarcoma oncogene homolog B) as the negative regulator of OC maturation (14,15). In addition, IL)17A regulates the OC polarization and bone remodelling priming the CEBPB expression for the balance of Lip/Lap isoforms while restrains experimental and human osteoclastogenesis by MAFB up)regulation (14).…”
mentioning
confidence: 99%
“…In addition, IL)17A regulates the OC polarization and bone remodelling priming the CEBPB expression for the balance of Lip/Lap isoforms while restrains experimental and human osteoclastogenesis by MAFB up)regulation (14). CEBPB controls the proliferation and differentiation of OCs as well as of other cell types through the alternative translation)initiation at distinct in frame start sites of Lap and Lip isoforms ( ").…”
mentioning
confidence: 99%